Analysis of Environmental Management Policy Strategies Due to Increased Land Built in Pekanbaru City - Bobby Masnur; Edi Rusdiyanto; Abdillah Munawir (Publikasi Indonesia, 2024)
The increase in built-up land in Pekanbaru City is a complex phenomenon that has a broad impact on the urban environment. This study aims to analyze the formulation of appropriate environmental management strategies in response to this trend. Using the Analytical Hierarchy Process (AHP) method, the study identified land changes between 2010 and 2022. Data from the Ministry of ATR/BPN shows a significant decrease in forest area or thickets, while built-up areas have increased, especially in Tampan and Tenayan Raya Districts. The results of the analysis show that effective policy strategies in managing the environment related to developed land must pay attention to environmental stewardship, economic collaboration, ecological citizenship movements, and community participation. Policy strategy recommendations should focus on effective policy implementation, strengthening economic collaboration, biodiversity conservation, and community empowerment in environmental decision-making. It is hoped that these strategies can improve the quality of the built land environment and overall improve the welfare of the people of Pekanbaru City.